Identification Procedures and Teacher Competencies for Teaching Students with Learning Disabilities: A Model for Indonesian Elementary Schools - Imanuel Hitipeuw (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1998)
This study was to investigate identification procedures and teacher competencies for teaching students with learning disabilities. The researcher reviewed professional literature and conducted a survey among volunteered students in two graduate classes. Literature review indicated that identification procedures promoted by professionals and governments had more similarities than differences. The models of the procedures clarified many aspects of the federal regulations and added much information on how to identify the students. Then the researcher developed and modified a model of identification procedures to meet the need of such procedures in Indonesian Elementary School. Survey indicated that the items of the survey represented the knowledge of teacher competencies and the results were modified into the same form for use in Indonesia.